Revestimento pelo processo eletrodo revestido com aço inoxidável 308L - Prado, Juliane Carla Lopes (2017)
One of the most efficient ways of improving surface properties of parts and components of industrial equipment has been, over time, the application of coatings. The large amount of available materials that can be applied in coatings has been more studied and gaining diverse applications and techniques of deposition, being the welding is one of the most used processes. In this work the welding current and the angle of the workpiece were varied and a study was made of how they interfere in the morphology of the weld bead and the hardness of the coatings being used as base metal a 1020 steel and addition metal a 308L steel through of Covered Electrode Welding.